STRATEGI KOMUNIKASI AJI BOJONEGORO DALAM MENCEGAH PRAKTIK JURNALISME AMPLOP - Moebin, Amrullah Ali (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2020)
Abstract This study discusses the communication strategy undertaken by the Alliance of Independent Journalists (AJI) Bojonegoro East Java in conducting discussions about the practice of envelope journalism. The reason is that the practice of envelope journalism violates the journalistic code of ethics. The research process uses qualitative methods with a case study approach. The results of this study are AJI Bojonegoro's strategy to prevent envelope journalism by creating new innovations. They provide education to the speakers. The media used is outdoor media, posters. Steps taken by interpersonal communication and utilizing social media. Keywords: Communication Strategy, Envelope Journalisme